The returns to participation in the nonfarm sector in rural Rwanda - Paternostro, Stefano (Policy research working paper, 2004)
"Dabalen, Paternostro, and Pierre investigate the differences in outcomes (earnings and consumption) between individuals (households) who participate in the nonfarm sector and those who do not. They use propensity score matching methods where they create appropriate comparison groups of individuals and households. First the authors find that nonfarm self-employed individuals in rural Rwanda have significantly higher earnings than farm workers and nonfarm formal employees. Second, they show that the benefits to nonfarm self-employment are much higher among the nonpoor than among the poor. Third, the authors show that diversified households--those with a farm and a nonfarm enterprise--are less likely to be poor. Finally, farm households who do not participate in the market have significantly lower consumption levels than households that do. However, the benefits to market participation appear to matter less for the poor than for the nonpoor. The authors find little difference in expenditures between market participants and nonmarket participants for comparable households in the bottom 40 percent of the expenditure distribution. This paper--a product of the Poverty Reduction Group, Poverty Reduction and Economic Management Network--is part of a larger effort in the network to understand rural nonfarm employment determinants"--World Bank web site